2002
DOI: 10.1364/ao.41.005002
|View full text |Cite
|
Sign up to set email alerts
|

Application of a high-repetition-rate laser diagnostic system for single-cycle-resolved imaging in internal combustion engines

Abstract: High-repetition-rate laser-induced fluorescence measurements of fuel and OH concentrations in internal combustion engines are demonstrated. Series of as many as eight fluorescence images, with a temporal resolution ranging from 10 micros to 1 ms, are acquired within one engine cycle. A multiple-laser system in combination with a multiple-CCD camera is used for cycle-resolved imaging in spark-ignition, direct-injection stratified-charge, and homogeneous-charge compression-ignition engines. The recorded data rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Exposure times, gains and trigger delays are individually programmable for each CCD, providing full timing control. More details of the laser cluster and the camera system can be found in [15].…”
Section: Methodsmentioning
confidence: 99%
“…Exposure times, gains and trigger delays are individually programmable for each CCD, providing full timing control. More details of the laser cluster and the camera system can be found in [15].…”
Section: Methodsmentioning
confidence: 99%
“…To probe electronic transitions of gasphase molecules, the use of optical parametric oscillators (OPOs) [1][2][3][4] or high-speed-pumped dye lasers [5] has been demonstrated. High-speed detection of species with mole fractions at the parts per million (ppm) level (e.g., the CH radical) necessitates the use of burst-mode-laser pump sources due to the limited availability of highspeed, short-pulse (10 ns) oscillators with sufficient perpulse laser energy.…”
mentioning
confidence: 99%
“…High-speed detection of species with mole fractions at the parts per million (ppm) level (e.g., the CH radical) necessitates the use of burst-mode-laser pump sources due to the limited availability of highspeed, short-pulse (10 ns) oscillators with sufficient perpulse laser energy. In addition, gain depletion in dye lasers limits output energy of multiple-pulse sequences [1]. Because of this, both custom-built [2,4] and commercially available burst-mode OPO instruments [3] have been used to produce wavelength-tunable UV or near-UV radiation.…”
mentioning
confidence: 99%
“…This study clearly demonstrated the value of fully 3D velocity vectors, obtained from stereoscopic PIV, in avoiding ambiguities due to out-of-plane motion. The eight-pulse burst laser was also used to study cycle-to-cycle variations in internal combustion engines [48]. Sequences of fuel tracer or OH radical distributions were monitored during single engine cycles.…”
Section: Literature Review Of Planar High-speed Plif and Piv In Combumentioning
confidence: 99%